Analisis Kemampuan Guru PAI Mengembangkan Media Pembelajaran Video: Studi Pada SMP Negeri 2 dan 4 Tanjung Pura - Ahmadi, Salman; Salminawati, Salminawati; Haidir, Haidir (Cetta: Jurnal Ilmu Pendidikan, 2024)
This research is motivated by the situation that PAI teachers in junior high schools should be able to master the learning that will take place. One of them is mastering the application of media in learning. Researchers want to explore the analysis of PAI Teachers' Ability to Develop Video Learning Media, studying at State Junior High Schools 2 and 4 Tanjung Pura. The type of research used is descriptive qualitative research with a multisite study approach. Qualitative research is a research method used to provide a detailed description of the research object. The research subjects consisted of principals, teachers and students of SMPN 2 Tanjung Pura and SMPN 4 Tajung Pura. The research uses interview, observation and documentation data collection techniques. The data analysis used is data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that planning for learning media management at SMPN 2 Tanjung Pura and SMPN 4 Tajung Pura is carried out by each teacher who will teach the learning material. This implementation includes procurement of learning media, storage, implementation and evaluation. Implementation in developing video learning media, using video media related to subject activities. Video media in subject activities is adjusted to the subject matter that will be provided. Evaluation of PAI teachers in developing video learning media at SMPN 2 Tanjung Pura and SMPN 4 Tanjung Pura is carried out by the Principal as educational supervision together with teachers in charge of each subject. Evaluation indicators are adjusted to competency standards and basic competencies that have been established in quality standards.